Գյուտարարական մակարդակը որպես գյուտի հատկանիշ - Ֆարմանյան, Ս.
И в государственных и в международных правовых актах существуют юридические неточности об изобретательском уровне. Но устранение этих неточностей является не проблемой законодателя, а проблемой практики, в связи с чем применение международной практики может иметь важное значение для Армении. The progress of science and technology is provided by inventive step of the invention. Both in the state and the international legal acts there are legal inaccuracies relating to inventive step. Removing these inaccuracies is not the problem of the legislative body, they are to be solved with the practice, and therefore the application of international practices can be important for Armenia.
Keywords: Իրավագիտություն